The Effect of Company Policy on Employee Compliance with the Implementation of AI to Maintain Company Data Security - Evan Haviana; Nina Dwi Putriani; Putri Wahyu Novika; Arko Pujadi; Nurlaila Syarfiah Asfo (Universitas Muhammadiyah Palu, 2025)
The rapid advancement of artificial intelligence (AI) in corporate data security presents both opportunities and challenges, particularly in ensuring employee compliance with security policies. This study aims to analyze the influence of corporate policies on employee adherence to AI-driven data security measures, focusing on how well-implemented policies can enhance awareness and compliance. Using a quantitative survey approach, data were collected from 200 employees working in companies that integrate AI into their security systems. Multiple linear regression analysis was employed to examine the relationship between corporate policies and employee compliance, with employee perceptions of AI serving as a moderating variable. The findings reveal that clear policies and comprehensive training programs have a significant positive impact on employee compliance with data security regulations. Furthermore, employee perceptions of AI moderate this relationship, indicating that those with a more positive understanding of AI are more likely to comply with established security policies. The study concludes that AI implementation for data security must be supported by strong corporate policies, effective training systems, and clear communication between management and employees. Companies must ensure that AI adoption not only strengthens data security but also addresses ethical and privacy concerns to foster trust and compliance among employees.